Religiosidade, adesão e qualidade de vida em pessoas vivendo com AIDS em uso de antirretrovirais - Fiuza, Maria Luciana Teles (2012)
The general aim was to assess the contribution of religiosity to the effectiveness of adherence and quality of life in people under antiretroviral therapy. A cross-sectional study with a quantitative approach was developed at the outpatient clinic for infectious diseases of Hospital Universitário Walter Cantídio (HUWC) at Universidade Federal do Ceará, Brazil. Participants were 215 people infected by HIV and under antiretroviral therapy (ARVT) between March and June 2012. A structured interview was used to collect sociodemographic and clinical data, and three instruments were applied: the Antiretroviral treatment adherence assessment questionnaire (CEAT-VIH), which consists of 20 items; the Quality of life assessment questionnaire (WHOQOL-HIV Bref), including six domains: and the Duke Religious Index – Durel, comprising three dimensions: Organizational Religiosity (OR), Non-Organizational Religiosity (NOR) and Intrinsic Religiosity (IR). The collected data were analyzed using STATA v.11. Total scores for the main characteristics were described and stratified according to the adherence levels. Bivariate analyses were performed and different tests were applied to compare proportions and correlations.To evaluate the internal consistency of the answers to the instrument items, Cronbach’s Alpha coefficient was used. To assess adherence, prevalence and the Prevalence Ratio were used. In all analyses, statistical significance was set at 5%. The study received approval from the research ethics committee at HUWC. The results demonstrated that the women were 45% less adherent than the men. Adherence levels are approximately three times lower among people between 50 and 59 years of age. Being heterosexual, gaining a lower income, having less years of education and being unemployed, having three or more children and living with four people or more are situations that indicate lower adherence levels. As regards adherence to antiretroviral therapy and religiosity, it was observed that shorter time for private religious activities also reduces adherence levels. As regards religiosity and quality of life, a possible relation exists between physical conditions and increased participation in religious meetings. Counting on social support can enhance attendance of religious meetings. People who participate in private religious activities show higher levels of personal, religious and spiritual beliefs. Concerning the relation between adherence and quality of life, distinctions are found between the quality of life domains and adherence groups (inappropriate/appropriate). In conclusion, being a woman, living on a low income, lower education level, older age, more children and living with different people entail an inappropriate adherence level to ARVT.As evidenced, the influence of religiosity on adherence is restricted, while adherence substantially affects quality of life.